Does sense of place matter? Investigating the role of airport atmospherics on destination revisit - Yerimou, Pantelitsa; Themistocleous, Christos; Panigyrakis, George G. (My University, 2022)
Despite the significance of airport atmospherics and visitors’ experiences, relatively few studies address the effect of both the airport environment and experience on the intentions to revisit the destination. This study draws new insights by examining (1) the influence of airport atmospherics on airport experience and willingness to revisit a destination, and (2) the effect of the overall experience evaluations on the intentions to revisit the host country. Sense of place’s moderating role on the relationship between atmospherics, experience and destination revisit is also examined. After a pre-test focus group with airport marketing executives, a main survey study was employed comprised of 604 international travelers. The proposed framework was tested through Structural Equation Modelling. In light of the study’s findings, it was revealed that airport atmospherics serve as strong indicators of overall experience evaluations as well as of the willingness to revisit the destination. Additionally, evidence indicate that sense of place did not have a moderating effect in the aforementioned relationships, with respective managerial implications concerning the use of atmospheric stimuli in the airport context and recommendations for future research being provided.
Keywords: Tourism; Atmospherics; Sense of Place; Airport Marketing